American legislative leaders in the South, 1911-1994 - Sharp, James Roger, 1936-; Sharp, Nancy Weatherly (Gale virtual reference library., 1999)
A biographical dictionary of state house speakers from 1911 to 1994. Covers speakers from Alabama, Arkansas, Florida, Georgia, Kentucky, Louisiana, Maryland, Mississippi, North Carolina, Oklahoma, South Carolina, Tennessee, Texas, Virginia, and West Virginia.